RESEARCH ON THE TOPIC OF (THE ROADMAP FOR TRANSFORMING TO CLEAN ENERGY TO DECREASE POLLUTION ARISING FROM OIL- RELATED ACTIVITIES) - MOHAMMED SHAKER BARAD ALI; DR. Qasswar falih shanyoor alsafi (Scholar Express Journals, 2025)
The strategy of transitioning to renewable energy has become of paramount importance to humanity because the amount of pollution resulting from oil activity has reached unprecedented levels and is negatively impacting human life. This pollution has led to environmental diseases, posing a significant threat to human life. These diseases could potentially kill a third of humanity due to illnesses caused by carbon emissions and toxic gases. Therefore, the need to transition to clean energy and create a new environment for human life has become urgent. Implementing this transition should become an international law imposed on all countries, guiding them towards alternative energy sources such as solar, wind, hydroelectric, geothermal, and bioenergy produced from organic materials like plants or agricultural waste. Other energy sources, such as tidal power, are also included. All of these energy sources reduce carbon emissions and air pollution, protect the environment, and play a vital role in combating climate change. Operating these energy sources will create numerous job opportunities in various sectors using clean energy and will also protect the marine environment from oil waste, which causes the death of marine life, birds, and animals. Liquid oil also contributes to Soil pollution contributes to the killing of living organisms and plants. After a period of time, millions of living organisms will become extinct, and as a result, humans will not be safe on the surface of the earth due to the pollution resulting from oil activity and toxic emissions resulting from harmful chemical reactions. The reason is due to the failure of countries to exploit alternative energies that replace oil, which is considered by some countries to be the main source of their global economy, providing them with a source of huge financial returns compared to other energies
Keywords: replace oil; countries; reason; economy